Integrating human papillomavirus vaccination into maternal, newborn, and child health week in Abia State, South-East Nigeria: a programmatic experience - Amuzie, Chidinma I.; Kalu, Kalu U.; Jibrin, Alkasim M.; Onwochei, Victoria N.; Ukonu, Victor; Naiya, Ahmed M.; Bassi, Amos P. (International Journal Of Community Medicine And Public Health, 2025)
Background: Despite being preventable, cervical cancer incidence continues to rise amid ongoing interventions. Following the introduction of the single-dose human papillomavirus (HPV) vaccine in October 2023, Nigeria has faced several challenges. Integrating HPV vaccination into the Maternal Newborn and Child Health Week (MNCHW) is a potential strategy to increase HPV vaccine uptake. Our objective was to assess the feasibility, acceptability, and operational processes of integrating HPV vaccination into MNCHW. Methods: This was a descriptive, cross-sectional study among the immunization and nutrition program officers at the State and LGA levels. Secondary data from the final MNCHW call-in data were retrieved and data on HPV vaccine doses given were extracted for analysis. Open data kit (ODK) collect forms were used to obtain data from the respondents. The IBM Statistical Product and Service Solutions (SPSS) version 26 was used for data analysis. Results: A total of 93 program officers participated in the survey. The mean age was 44.8±8.0 years. Females constituted 76.3% and the majority (94.8%) were from the LGA level. A total of 30,523 HPV vaccine doses were reported on DHIS2 for June, representing a five-fold increase compared to pre-integration months. The most prevalent challenges reported were inadequate funding (24%) and team insufficiency (24%). Most (95.6%) had overall satisfaction with the program. Conclusions: The integration of HPV vaccination into the MNCHW in June significantly improved HPV vaccine uptake. Most respondents were satisfied with the integration. Programmatic challenges and areas of improvement were noted. It is recommended that this integrative approach be sustained, scaled up, and further strengthened to maximize its impact in Abia State.